Pelvic Floor Muscle Training Program in Pregnant Nepalese Women- A Feasibility Study - Achary, Ranjeeta Shijagurumayum; Tveter, Anne Therese; Grotle, Margreth; Khadgi, Bimika; Eberhard-Gran, Malin; Braekken, Ingeborg H.; Stuge, Britt (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Obstetric Fistula is one of the common pelvic floor dysfunctions that affects the women’s quality of life. PFMT is recommended as first line treatment for prevention and treatment of pelvic floor dysfunctions. There is lack of knowledge on the feasibility of performing a PFMT program in pregnant Nepalese women. The aim was to develop a Pelvic floor muscle training (PFMT) program and to assess the feasibility of the program by assessing attendance to antenatal follow-up visits and adherence to PFMT. Methods: The PFMT program included development of education material (video, leaflet, and poster) and PFMT in different positions. Pregnant women (before 16 weeks of gestation) visiting Dhulikhel Hospital were recruited consecutively. Sociodemographic factors, pregnancy history, symptoms of urinary incontinence, pelvic organ prolapse and depression questionnaires were collected at first and last visit. Number of antenatal follow-up visits, exercise diary records and motivation questions for performing PFMT were also collected.Compliers were defined as women attending four or more PFMT antenatal follow-up visits. Results: Two hundred and fifty three pregnant women with mean age25 (Standard deviation, (SD) 4) years and mean gestation weeks of 10(SD 3) were included. In total, 164 (65%) participants complied with the PFMT program and 89 (35%) did not comply.Eight percent of the women reported not doing PFMT and approximately 20% women over-reported to have performed PFMT. Conclusions: More than half of the women completed the PFMT program. Adherence to PFMT had inconsistent results.